Analisis Wacana Alternatif Analisis Teks Media - Irta Sulastri (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2004)
Some people have a notion that mass media has never and will not more giving fact or truth "naturally " In reading a text, we have done imaginative dialogued with its author, not only living in range of time but also living in different place. That why, here we get into a hermeneutik thought. This article will offer analyse discourse approach, not only related to written and text discourses, but also context discourses.